A Model Of Internalizing Religious Moderation Values In Haromain Tahfidz Boarding School Pekanbaru - Maralottung Siregar; Aini Qolbiyah; Bilhakk Putra; Roni Putra; Edi Azhar (Pendidikan Agama Islam Institut Agama Islam Diniyyah Pekanbaru, 2026)
This study aims to examine the implementation of a model for internalizing the values of religious moderation within the tahfiz education system at Pondok Tahfiz Haromain. The study employs a qualitative case study design. Data were collected through classroom and dormitory observations, reflective notes, and semi-structured interviews with teachers, dormitory supervisors, and students. The analysis focused on three main components of the model: talaqqi-based tahfiz learning, bilingual education using Arabic and English, and habit-forming practices integrated into daily life. The results indicate that values of religious moderation such as balance, tolerance, responsibility, and empathy can be effectively internalized through intensive interactions between teachers and students during talaqqi sessions, bilingual learning practices, and various routine activities such as congregational worship, reflective discussions, and joint social service. These integrated practices strengthen the students’ ability to memorize the Qur’an and support the formation of a moderate and inclusive religious character. This study contributes by offering an integrative model that links tahfiz education with character development and religious moderation within the pesantren environment.